2015
DOI: 10.5539/gjhs.v8n6p25
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Growth Factor-β and Interferon-γ Serum Levels With Insulin Resistance in Normal Pregnancy

Abstract: Pregnancy is related to change in glucose metabolism and insulin production. The aim of our study was to determine the association of serum IFN-γ and TGF-β levels with insulin resistance during normal pregnancy. This cross sectional study was carried out on 97 healthy pregnant (in different trimesters) and 28 healthy non-pregnant women. Serum TGF-β and IFN-γ level were measured by ELISA method. Pregnant women had high level TGF-β and low level IFN-γ as compared non-pregnant women. Maternal serum TGF-β concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, a decrease in IL-17A production was observed in decidual T cells compared to peripheral blood T cells (110). Pregnant women had high level TGF-β and low level IFN-γ as compared to non-pregnant women (111). Projecting from the effects of lactic acid on immune cells in the tumor microenvironment, lactic acid generated in the first trimester of pregnancy could play an important role in immune regulate functions, potentially by decreasing the cytotoxic activity of T cells and NK cells, promotes Th2-type and regulate the polarization of DM.…”
Section: The Possible Role Of Lactic Acid At the Maternal-fetal Intermentioning
confidence: 88%
“…Furthermore, a decrease in IL-17A production was observed in decidual T cells compared to peripheral blood T cells (110). Pregnant women had high level TGF-β and low level IFN-γ as compared to non-pregnant women (111). Projecting from the effects of lactic acid on immune cells in the tumor microenvironment, lactic acid generated in the first trimester of pregnancy could play an important role in immune regulate functions, potentially by decreasing the cytotoxic activity of T cells and NK cells, promotes Th2-type and regulate the polarization of DM.…”
Section: The Possible Role Of Lactic Acid At the Maternal-fetal Intermentioning
confidence: 88%
“…In fact, concomitantly with the increase in TGF-β1 in proportion to the increase in BMI, we observed a significant increase in insulin, glucose, HbA 1c and HOMA-IR levels and a significant decrease in IS, suggesting that this cytokine could play an important role in the development of IR in patients with excess weight. Previous studies have shown that TGF-β contributes to the development of IR in pregnant women [27][28][29] .…”
Section: Discussionmentioning
confidence: 98%